DAYA LITERASI PENGAJAR BAHASA INDONESIA BAGI PENUTUR ASING PADA ERA DISRUPSI DAN REVOLUSI INDUSTRI 4.0 - Park Jin Ryeo (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The concrete problems which are the main topics in this paper are the challenges of the instructor in creating learning Indonesian as a foreign language that is effective in the era of the Industrial Revolution 4.0. The content includes the teaching of Indonesian in the Indonesian-Malaysian Language Study Program, the Busan University of Foreign Studies (BUFS), about the problem of learning Indonesian for foreign speakers, and the challenges of teaching Indonesian in the Industrial Revolution 4.0 era as well as Indonesian literacy literacy in the Disruption Era